1991
DOI: 10.1002/smj.4250120103
|View full text |Cite
|
Sign up to set email alerts
|

Organizing competitor analysis systems

Abstract: Based on a detailed study of the competitor analysis (CA) systems in three large companies, this paper examines the assessments of the formal CA system by its members and its major users, the uses to which CA is put, and the organizational systems by which the function attempts to improve its contribution and strengthen its role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 7 publications
2
123
0
5
Order By: Relevance
“…Ghoshal and Westney (1991) found that among both analysts and clients of competitive intelligence, the limited time for analysis was a significant barrier to sense-making efficacy. Fuld (1991) proposes that the lack of time to nurture and analyze data is an important reason for the failure of many CI programs.…”
Section: Time Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghoshal and Westney (1991) found that among both analysts and clients of competitive intelligence, the limited time for analysis was a significant barrier to sense-making efficacy. Fuld (1991) proposes that the lack of time to nurture and analyze data is an important reason for the failure of many CI programs.…”
Section: Time Allocationmentioning
confidence: 99%
“…2 This is particularly true since current research on competitive intelligence is often not grounded in observations from actual practice (for an exception, see Ghoshal and Westney, 1991).…”
mentioning
confidence: 99%
“…The interest of sharing information from S.Scan is not understood The structures for the dissemination of information are inadequate Englewod & Lenz, 1985;Ghoshal & Westney, 1991;Lesca & Caron-Fasan, 2008.…”
Section: Poor Circulation Of Informationmentioning
confidence: 99%
“…An organizational culture hostile to or unwilling to share and circulate information Diffenbach, 1983;Englewod & Lenz, 1985;Ghoshal & Westney, 1991;Babbar & Rai, 1993;Lesca & CaronFasan, 2008. …”
Section: Hostile Organizational Culturementioning
confidence: 99%
“…There has been support for this awareness/culture construct in the area of market orientation (Gelb et al, 1991;Ghoshal and Kim, 1986;Ghoshal and Westney, 1991;Kohli and Jaworski, 1990;Narver and Slater, 1990;Pole et al, 2000;Slater and Narver, 1994, 2000.…”
Section: Organisational Awareness/culturementioning
confidence: 99%